Association of socioeconomic factors and the risk for unintentional injuries among children in Japan: a cross-sectional study. Issue 8 (13th August 2018) - Sato, Nobuhiro; Hagiwara, Yusuke; Ishikawa, Junta; Akazawa, Kohei
Abstract : Objectives: While Japan has socioeconomic issues, such as income inequality, little is known about the association between socioeconomic factors and the risk of unintentional childhood injuries. The purpose of the study was to evaluate the influence of socioeconomic factors on the risk for unintentional injuries among preschool children in Japan. Design: Cross-sectional study using data from a web-based questionnaire survey. Setting: Japan (January 2015). Participants: 1000 households with preschool children under 6 years of age. Outcome measures: Multivariate logistic regression was performed to analyse the influence of socioeconomic factors on the incidence of unintentional injuries. Results: Overall, 976 households were eligible for the analysis, with 201 households reporting unintentional injuries. The incidence rates for unintentional injury were estimated to be constant across all strata constructed using combinations of socioeconomic factors. The multivariate logistic regression analysis showed no significant differences in socioeconomic factors between households that reported unintentional injuries and those that did not. Conclusion: The findings of our study demonstrated that unintentional injuries among preschool children occurred at approximately fixed rates, independent of socioeconomic factors. Accordingly, prevention strategies for unintentional injuries that concern socioeconomic disadvantages should be avoided in Japan.